An alternatively transcribed TAZ variant negatively regulates JAK‐STAT signaling. (12th April 2019) - Fang, Chuantao; Li, Jian; Qi, Sixian; Lei, Yubin; Zeng, Yan; Yu, Pengcheng; Hu, Zhaolan; Zhou, Yufeng; Wang, Yulong; Dai, Ruping; Li, Jin; Huang, Shenglin; et al.
Abstract: Type I interferon (IFN)‐induced Janus kinase (JAK)–signal transducer and activator of transcription (STAT) signaling drives the expression of IFN‐stimulated genes (ISGs) to mediate antiviral response. The strength and duration of JAK‐STAT signaling are tightly regulated to ensure effective antiviral defense while avoiding pathological inflammation and autoimmunity. Here, we report that cTAZ, an isoform of the Hippo pathway effector TAZ, is transcribed by an alternative promoter. Although majority of C‐terminal sequences of TAZ is retained, cTAZ is not regulated by the Hippo signaling and does not mediate its growth‐inhibitory functions. Instead, cTAZ negatively regulates JAK‐STAT signaling by inhibiting STAT1/2 nuclear localization and ISG expression, and its expression is induced by type I IFN. Thus, cTAZ functions as a modulator of JAK‐STAT signaling and may play a role in fine‐tuning cellular antiviral response. Synopsis: JAK‐STAT signaling drives the expression of IFN‐stimulated genes to mediate antiviral immunity. A short TAZ variant, cTAZ, represses JAK‐STAT signaling and cellular antiviral responses in a Hippo pathway independent manner. cTAZ is a short TAZ variant transcribed from an alternative promoter. cTAZ is not regulated by the Hippo pathway and does not possess canonical Hippo pathway functions. cTAZ represses cellular antiviral response by inhibiting STAT1/2 dimerization and nuclear translocation. Abstract : JAK‐STAT signaling drives the expression of IFN‐stimulated genes to mediate antiviral immunity. A short TAZ variant, cTAZ, represses JAK‐STAT signaling and cellular antiviral responses in a Hippo pathway independent manner.